Tahapan dan Kendala Evaluasi Proses Pembelajaran di Lembaga Pendidikan Islam - Aulia, Dini Silmy; Bahrani; Akhmad Ramli (Institut Ummul Quro Al-Islami Bogor, 2024)
When the learning process is seen as a process of changing student behavior, the role of evaluating the learning process becomes very important. Therefore, this research will present the scope of Learning Process Evaluation and its five parts, namely Learning Planning Evaluation, Learning Implementation Evaluation, Learning Media Evaluation, Learning Method Evaluation, and Learning Assessment Evaluation as well as what are the obstacles during learning process evaluation in educational institutions. Islam goes on. The method used is the literature study method through collecting books, previous research and articles. The results show that the Learning Planning Evaluation was carried out using summative and formative evaluations, as well as revising the learning program. Evaluation of learning implementation by assessing classroom and student management as well as teacher management. Evaluation of Learning Media with formative evaluation and summative evaluation. Evaluate Learning Methods by assessing their suitability to basic competencies and learning outcomes, class or school conditions, students' level of development, teacher abilities, and time. Evaluation of Learning Assessment with assessment of learning achievement, performance, alternative, authentic and portfolio. The obstacles faced include a lack of teacher ability, skills and initiative, less varied learning methods, limited time, and a lack of collaboration between teachers in Islamic Education Institutions.